2023
DOI: 10.26434/chemrxiv-2023-n278x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elucidating Trivalent Ion Adsorption at Floating Carboxylic Acid Monolayers: Charge Reversal or Water Reorganization?

Abstract: We study trivalent neodymium adsorption on floating arachidic acid films at the air/water interface by two complementary surface specific probes, sum frequency generation (SFG) spectroscopy and X-ray fluorescence near total reflection (XFNTR). In the absence of background ions, neodymium ions compensate the surface charge of the arachidic acid film at 50 M bulk concentration without any charge reversal. Increasing the bulk concentration to 1 mM does not change the neodymium surface coverage but affects the in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…This is in contrast to the strong ion specific trends observed at the silica interface but agrees well with the indistinguishable behavior of these salts at AA monolayers [18]. In recent years, many studies demonstrated that the surface characteristics play an important role in ion-specific effects, and it is not trivial to generalize the observations in one specific system to others [32,49].…”
Section: Identifying Water Populations With Different Hydrogen Bondin...supporting
confidence: 83%
“…This is in contrast to the strong ion specific trends observed at the silica interface but agrees well with the indistinguishable behavior of these salts at AA monolayers [18]. In recent years, many studies demonstrated that the surface characteristics play an important role in ion-specific effects, and it is not trivial to generalize the observations in one specific system to others [32,49].…”
Section: Identifying Water Populations With Different Hydrogen Bondin...supporting
confidence: 83%
“…demonstrated with another light lanthanide, neodymium. 39 The intensity of this SFG peak, which is associated with dehydration, increases as the subphase concentration increases likely because there are more partially dehydrated La 3+ ions present. We speculate the carboxylic acid groups of AA can facilitate ion dehydration thus encouraging adsorption.…”
Section: La 3+ and Lu 3+ Hydration Structure During Adsorption To Gra...mentioning
confidence: 98%
“…38 X-ray scattering and molecular dynamics simulations 35 have shown a gradual transition from ~9 to ~8 waters in the first coordination shell from La 3+ to Lu 3+ . The hydration structure of ions at the air/water interface is directly relevant to separation efforts, as ions may undergo partial or total dehydration during adsorption 32,[39][40][41] . Recently, our group studied Nd 3+ adsorption to arachidic acid (AA) films using vibrational sum frequency generation spectroscopy (SFG) and observed a red-shifted signal within the water region, which was attributed to the partial dehydration of adsorbed Nd 3+ ions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32,39,40 Recently, our group studied Nd adsorption to arachidic acid (AA) films using vibrational sum frequency generation spectroscopy (SFG) and observed a red-shifted signal within the water region, which was attributed to the partial dehydration of adsorbed Nd ions. 41 SFG is an inherently surface-specific technique that is well suited to understand local water structures near the air/ water interface as the signal is only generated when centrosymmetry is broken (Figure 1). 39,40,42−44 In this work, we consider both light lanthanide La and heavy lanthanide Lu adsorption to a GO thin film and an ideal AA monolayer at the air/water interface to understand the effects of ion size on adsorption and local water structure.…”
Section: ■ Introductionmentioning
confidence: 99%